Improvement of smoked cull chicken (Gallus gallus domesticus var. anak) frankfurter - Villanueva, Carolina N.
Smoked cull chicken frankfurters were improved in terms of yield and product quality. The raw cull chicken (Anak variety) was characterized in terms of moisture content, protein content and fat content. From this, the amount of the meat and fat were adjusted to produce the desirable emulsion for the product. Development of product flavor was done by determining the best levels of salt and spice mix for the emulsion. Based on the sensory evaluation, the most acceptable level for the flavor of cull chicken frankfurters was at 4.0% salt and 3.0% spice mix by weight. The substitution of chicken fat to pork fat was studied as a possible means to increase yield and improve product quality. The best result in terms of finished product quality were obtained with the use of 100% pork fat. A high yield of 84% was also obtained from it. The optimum time and temperature for smoking in a Tory-Kiln smokehouse was established at a staged process of 55°C with 3°C increments every 10 minutes until internal temperature reaches 70°C. The product cost was determined to be P28.64 per kilogram.